Social Life and Everyday Experience of Ethnic People in Urban Setting: An Anthropological Overview of Darai People of Damauli Bazaar - Kaini, Tika Raj; Shree, Bishista (NUTA Journal, 2020)
This paper investigates the issues of urban development and the quality of life of Darai people with the process of modernization. It explores the process of urbanization and distribution of land after the planning in urban area. The paper highlights issues of ethnic solidarity, tensions and situation of utilization of modern facilities among the Darai ethnic population of Damauli Bazaar. Findings of this research point out the overall dissatisfaction with inadequate facilities, fear of ethnic tensions, exclusion from social processes and division in ethnic solidarity among the studied population.